H-ferritin ferroxidase induces cytoprotective pathways and inhibits microvascular stasis in transgenic sickle mice - Vercellotti, Gregory M.; Khan, Fatima B.; Nguyen, Julia; Chen, Chunsheng; Bruzzone, Carol M.; Bechtel, Heather; Brown, Graham; Nath, Karl A.; Steer, Clifford J.; Hebbel, Robert P.; Belcher, John D. (Frontiers in Pharmacology, 2014)
Hemolysis, oxidative stress, inflammation, vaso-occlusion and organ infarction are hallmarks of sickle cell disease (SCD). We have previously shown that increases in heme oxygenase-1 (HO-1) activity detoxify heme and inhibit vaso-occlusion in transgenic mouse models of SCD. HO-1 releases Fe2+ from heme, and the ferritin heavy chain (FHC) ferroxidase oxidizes iron to catalytically-inactive Fe3+ inside ferritin. FHC overexpression has been shown to be cytoprotective. In this study, we hypothesized that overexpression of FHC and its ferroxidase activity will inhibit inflammation and microvascular stasis in transgenic sickle mice in response to stroma-free hemoglobin. We utilized a Sleeping Beauty transposase plasmid to deliver a human wild-type-ferritin heavy chain (wt-hFHC) transposable element by hydrodynamic tail vein injections to NY1DD SCD mice. Control mice were infused with the same volume of lactated Ringer's solution (LRS) or a triple missense human FHC (ms-hFHC) plasmid with no ferroxidase activity. Eight weeks later, LRS-injected mice had ~40% microvascular stasis (% non-flowing venules) when infused with stroma-free hemoglobin at 1 h, while mice overexpressing wt-hFHC had only 5% stasis (p< 0.05), and ms-hFHC mice had 33% stasis suggesting vascular protection by ferroxidase active wt-hFHC. The wt-hFHC SCD mice had marked increases in splenic hFHC mRNA and hepatic hFHC protein, light chain ferritin, 5-aminolevulinic acid synthase (5-ALA-synthase), heme content, ferroportin, nuclear factor erythroid 2-related factor 2 (Nrf2), nuclear hFHC, and microsomal HO-1 activity and protein, and a decrease in activated nuclear phosho-nuclear factor-kappa B (NF-κB) p65. HO-1 activity was not essential for the protection by FHC. We conclude that wt-hFHC ferroxidase activity enhances cytoprotective Nrf2-regulated proteins including HO-1, thereby resulting in decreased NF-κB-activation, inflammation and microvascular stasis in transgenic SCD mice.